2011
DOI: 10.1080/14786419.2010.529546
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant activity of some lichen metabolites

Abstract: Antioxidant activity of several classes of lichen metabolites were assessed in the in vitro superoxide radical (SOR), nitric oxide radical and 2,2-diphenyl-1-picrylhydrazil radical scavenging assays. The despsides sekikaic acid and lecanoric acid showed promising antioxidant activity in SOR assay with IC₅₀ values of 82.0 ± 0.3 µmol and 91.5 ± 2.1 µmol, respectively, while the depsidone lobaric acid exhibited an IC₅₀ value of 97.9 ± 1.6 µmol, all relative to the standard, propyl gallate (IC₅₀ = 106.0 ± 1.7 µmol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
96
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(101 citation statements)
references
References 32 publications
3
96
0
2
Order By: Relevance
“…Arg. ), Motyka (Parmeliaceae) (Behera et al, 2012), Usnea ghattensis (Verma et al, 2008b), psoromic and usnic acids (Behera et al, 2012), and on other 14 lichenpurified metabolites (Thadhani et al, 2011). Moreover, hydrogen peroxide scavenging activity was investigated on Parmelia saxatilis (Ö zen & Kinalioglu, 2008) and the TEAC value (Trolox equivalent antioxidant capacity) has been determined using the ABTS radical assay in several polar lichen species Singh et al, 2011), as well as in Usnea ghattensis (Behera et al, 2005a;Verma et al, 2008a), Laurera benguelensis Zahlbr.…”
Section: Antioxidant Properties Of Lichensmentioning
confidence: 99%
“…Arg. ), Motyka (Parmeliaceae) (Behera et al, 2012), Usnea ghattensis (Verma et al, 2008b), psoromic and usnic acids (Behera et al, 2012), and on other 14 lichenpurified metabolites (Thadhani et al, 2011). Moreover, hydrogen peroxide scavenging activity was investigated on Parmelia saxatilis (Ö zen & Kinalioglu, 2008) and the TEAC value (Trolox equivalent antioxidant capacity) has been determined using the ABTS radical assay in several polar lichen species Singh et al, 2011), as well as in Usnea ghattensis (Behera et al, 2005a;Verma et al, 2008a), Laurera benguelensis Zahlbr.…”
Section: Antioxidant Properties Of Lichensmentioning
confidence: 99%
“…Usnic acid, salazinic acid, and atranorin are the major compounds reported in this study which have several important biological roles. These compounds have strong antimicrobial property [30][31][32], anticancerous properties [33], antiherbivorous [34],; antioxidants [35,36], and immunomodulatory [37]. Almost all the metabolites identified in the TLC results of this study have also been reported as sources of commercial dyes [38].…”
Section: Ramya and Thirunalasundarimentioning
confidence: 69%
“…A remarkable feature of lichen species is their antioxidant capacity that resides in their phenolic moieties [31]. Interestingly, some depsides and depsidones isolated from lichens have shown antioxidant capacity [32][33][34]. Besides this, neuroprotective effect and cytotoxic potential have been described in Cetraria islandica and Vulpicida canadensis [35].…”
Section: Lichens As Antioxidants and Tau Inhibitors Sourcementioning
confidence: 99%